Arab Republic of Egypt : Third Review Under the Extended Arrangement Under the Extended Fund Facility, and Requests for a Waiver of Nonobservance of a Performance Criterion and for Modification of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report, 2018)
Macroeconomic conditions have continued to improve during 2017/18, with external and fiscal deficits narrowing, inflation and unemployment declining, and growth accelerating. The near-term growth outlook is favorable, supported by the recovery in tourism and rising natural gas production, while the current account deficit has fallen below 3 percent of GDP and gross international reserves stood at 7 months of prospective imports at end-May. Inflation is expected to temporarily rise in 2018/19, reflecting increases in fuel and electricity prices, but the monetary policy stance appears appropriate to contain second-round effects. The government debt ratio is projected to decline markedly in response to fiscal consolidation and high nominal GDP growth.